The Watercolors of Harlan Hubbard - Morrin, Peter (Book collections on Project MUSE., 2021)
"Harlan Hubbard (1900-1988), a Kentucky writer, environmentalist, and artist, spent many years trying to rediscover and revive the vanishing language of landscape in his watercolor paintings. Known for their sense of drifting movement and their depiction of the natural way of life fondly associated with Hubbard, they inexplicably remain his least studied artworks, despite presenting some of the best evidence of Hubbard's place in the history of landscape painting. The Watercolors of Harlan Hubbard not only argues for Hubbard's place in the art historical canon but also highlights and analyzes the artist's own voice. In this unique collection, more than two hundred watercolors are interspersed with anecdotes from those who knew Hubbard or drew inspiration from his work, offering a personal meditation on a deeply influential artist and serving as an invitation to those who have yet to discover him"--